Using IBM DB2 UDB with IBM System Storage N series - Osuna, Alex; Lal, Jawarhar; Sanders, Roger; Brumer, Jeremy (IBM Redbooks, 2006)
Database cloning is the process by which you create an exact copy of a DB2 database, either by physically copying the data or by performing what is known as a redirected restore. Database cloning is performed frequently by database administrators to provide near-production data for various business needs such as application development, QA testing, and report generation. Traditional methods of cloning a database pose various challenges, including system downtime and degraded system performance during the cloning process. Additionally, a large amount of storage space is required to store each clone. Furthermore, the maintenance overhead can be enormous if each cloned database requires a frequent data refresh. This IBM Redbooks publication describes the process used to create a clone of an IBM DB2 UDB database using FlexClone technology. This book also covers creating a database clone on a disaster recovery site that has replicated data using Data ONTAP SnapMirror technology.